A Review on Location Aided Routing Protocol in Mobile Adhoc Networks (International Journal of Engineering and Computer Science, 2015)
Ad hoc networks are the decentralized network consisting of randomly moving nodes. One of the main tasks in these networks is routing of data packets. Many protocols have been proposed for routing of data packets among these nodes. Our goal is to explore the working and analyze the various aspects and parameters of position based LAR protocol. This protocol suggests an approach to utilize the location information for routing purpose. This approach is beneficial in reducing the search area and limits flooding as well as increases the throughput. Existing systems work on the idea of single source and single destination system but our focus is mainly on developing a system having single source and multipoint destination. This makes a significant impact on the throughput as well as end to end delay.